DISNEY PRINCESS : Little Golden Book favorites. (Golden Books, 2014)
Collects three stories starring Disney princesses, including "The Princess and the Frog," in which Tiana's hopes of opening a restaurant are dashed when she kisses a prince who has been turned into frog and she turns into a frog herself.